Inappropriate trusting behaviour in dementia - Chokesuwattanaskul, Anthipa; Penn, Dexter; Albero, Claudia; Johnson, Jeremy C. S.; Benhamou, Elia; Russell, Lucy L.; Hardy, Chris J. D.; Marshall, Charles R.; Rohrer, Jonathan D.; Warren, Jason D. (Frontiers in Neurology, 2024)
Background Inappropriate trusting behaviour may have significant social, financial and other consequences for people living with dementia. However, its clinical associations and predictors have not been clarified. Here we addressed this issue in canonical syndromes of frontotemporal dementia (FTD) and Alzheimer’s disease (AD). Methods In 34 patients with AD and 73 with FTD (27 behavioural variant (bv)FTD, 22 semantic variant primary progressive aphasia (svPPA), 24 nonfluent/agrammatic variant (nfv)PPA) we recorded inappropriate trusting and other abnormal socio-emotional behaviours using a semi-structured caregiver survey. Patients were comprehensively characterised using a general cognitive assessment and the Revised Self-Monitoring Scale (RSMS; an informant index of socioemotional awareness). Results Inappropriate trusting was more frequent in svPPA (55%) and bvFTD (44%) than nfvPPA (17%) or AD (24%). After adjusting for age, sex, education and Mini-Mental State Examination (MMSE) score, inappropriate trusting was significantly more likely in svPPA (odds ratio 3.61; 95% confidence interval 1.41–8.75) and bvFTD (3.01, 1.23–6.65) than AD. Significant predictors of inappropriate trusting comprised apathy in svPPA, disinhibition and altered pain responsiveness in bvFTD, and lower MMSE and RSMS (self-presentation) scores in AD. Conclusion Dementia syndromes vary in prevalence and predictors of abnormal trusting behaviour, with implications for clinical counselling and safeguarding.